2012
DOI: 10.1103/physreve.85.036313
|View full text |Cite
|
Sign up to set email alerts
|

Depinning and creeplike motion of wetting fronts in weakly vibrated granular media

Abstract: We study the effect of weak vibrations on the imbibition of water in granular media. In our experiments, we have observed that as soon as the vibration is applied, an initially pinned wetting front advances in the direction of imbibition. We found that the front motion is governed by the avalanches of localized intermittent advances directed at 45° to the imbibition direction. When the rescaled gravitational acceleration of vertical vibrations is in the range of 0.81≤G≤0.95, we observed an almost steady motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Imbibition is very important, since it is present in many daily activities, such as a drop of coffee on a napkin, wine filtering, fluid transport in plants, water penetration into concrete [1][2] or enhanced oil recovery [3][4][5], among others. However, an extensive research on imbibition processes is focused on the recovery of crude oil from naturally fractured reservoirs, either spontaneous imbibition [6][7] or forced imbibition [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Imbibition is very important, since it is present in many daily activities, such as a drop of coffee on a napkin, wine filtering, fluid transport in plants, water penetration into concrete [1][2] or enhanced oil recovery [3][4][5], among others. However, an extensive research on imbibition processes is focused on the recovery of crude oil from naturally fractured reservoirs, either spontaneous imbibition [6][7] or forced imbibition [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous capillary imbibition is a transport phenomenon present in a variety of technological applications such as oil recovery, building materials, soil science, textile and hydrology [1]. Due to this diversity of applications, an infinity of theoretical [2][3][4][5][6] and experimental [7][8][9][10][11][12][13][14] studies have been carried out based on the pioneering works of Lucas [15] and Washburn [16] in order to understand the imbibition mechanism and the related phenomena (for review, see [1,17,18], and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It was experimentally demonstrated that the imbibition speed becomes slower than that of Lucas-Washburn Regime (x ∝ √ t) [7][8][9][10][11][12][13][14] as a consequence of the heterogeneity of flow in porous media due to the complex network of randomly distributed pores that connect to each other forming tortuous capillaries through which fluid flows. This tortuous path has a fractal character and the Lucas-Washburn equation is scarce to model imbibition process in permeable materials that possess fractal architecture.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of paper wetting experiments is that the wetting front configurations are easily observable in situ, since the associated time and spatial scales are easily accessible in the laboratory studies. Although extensive experimental and theoretical research has been performed in the past decade to understand the dynamics and pinning of imbibition fronts in porous media [7,[12][13][14][15][16][17][18][19], several aspects of related phenomena remain unknown or poorly understood.…”
mentioning
confidence: 99%
“…with the scaling exponent in the range of 0.3 δ < 0.5 (see, for review, Ref. [24]), whereas the global front width increases as W ∝ t α , where α is the global growth exponent [14,19]. As the imbibition front advances, the net loss of water mass per unit time due to evaporation increases, because of an increase in the wetted area.…”
mentioning
confidence: 99%